2x * x^2 = 2x^3.
Multiply the parts that are alike. The first term has a coefficient of 2, the second term has a coefficient of 1 (x = 1*x). The first term has variable x (which is x^1), the second term has variable x^2. Since they have the same base (both are x), we can add the powers together (x^2 = x * x, so x * x^2 = x * x * x = x^3)
2x² multiplied by 5 = 10x²
2x to the fourth
No. x squared is x times x, whereas 2x is x + x.
(X2) (X2) = X4 x squared multiplied by x squared is x raised to the 4th power.
x times 2x is 2x squared or 2x2
3x squared - x squared = 2x squared
It's difficult to identify where the parentheses belong in the question. Here are the answers corresponding to a few possibilities: x (2x2) = 2x3 x (2x)2 = 4x3 (x Â· 2x)2 = 4x4
If you mean: (2x-7y)(x+y) then it is 2x squared -5xy -7y squared
x2 - 2x = x(x-2)
x(2x + 1)
(2x)2(x) = 4x3
2x2 ÷ x = 2x
It is: -2x squared
x² + 2x = x(x+2)
2x2 + 2x = 2x(x+1)
Add the x's squared together to get 2x^2+x. You cannot add anymore so the answer is 2x^2+x
x multiplied by 2 equals to 2x.
It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.
2 squared X 3 squared = 5 squared
2x squared plus 2x plus xy plus y or 2x(x+1) + y(x+1) or (x+1)(2x+y)